2006
DOI: 10.1007/s10964-006-9042-9
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Marital Expectations and Romantic Experiences: Associations With Perceptions About Parental Conflict and Adolescent Attachment Security

Abstract: This study tested associations between adolescent perceptions of interparental conflict, adolescent attachment security with parents, and adolescent marital expectations and romantic experiences. Participants were 96 early adolescent females from 2 parent families. Insecurity was examined as a mediator of the association between negative perceptions of parental conflict and romantic outcomes.Results supported the mediation model in which adolescents' negative perceptions of parental conflict was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 49 publications
4
60
0
2
Order By: Relevance
“…The SPPA has demonstrated good internal consistency as well as construct, convergent, divergent, and factorial validity in adolescent samples (Harter, 1988;Wichstrom, 1995). In our sample, Cronbach's alpha was .75.Romantic experiences-We used a self-report measure to assess participants' level of romantic experience (Steinberg, Davila, & Fincham, 2006). Items described common romantic experiences that may be considered normative for early adolescents, such as having flirted with someone, having been asked on a date, and having been kissed.…”
mentioning
confidence: 98%
“…The SPPA has demonstrated good internal consistency as well as construct, convergent, divergent, and factorial validity in adolescent samples (Harter, 1988;Wichstrom, 1995). In our sample, Cronbach's alpha was .75.Romantic experiences-We used a self-report measure to assess participants' level of romantic experience (Steinberg, Davila, & Fincham, 2006). Items described common romantic experiences that may be considered normative for early adolescents, such as having flirted with someone, having been asked on a date, and having been kissed.…”
mentioning
confidence: 98%
“…In a study of intraindividual and peer influences on sexual experience, all associations were mediated by romantic initiation (Zimmer-Gembeck et al 2004). We expect to find the same for the link between parent-child relations and sexual behavior, because parents appear to play a major role in romantic and sexual initiation as well (Davila et al 2009;De Graaf et al 2011;Steinberg et al 2006). Because positive family relations have been found to relate to both romantic and sexual initiation and because romantic and sexual initiation have been found to be closely interrelated, we expect early romantic initiation to mediate the association between family cohesion and an early sexual debut.…”
Section: Goals and Hypotheses Of The Present Studymentioning
confidence: 90%
“…Their energy is mainly focused outside the family. Adolescents originating from these kinds of homes possibly seek out romantic relationships earlier, because they are looking for support and closeness that is missing from the parent-child relationship (Davila et al 2009;Steinberg et al 2006). Ergo, both biological and psychosocial theories lead us to expect an association between negative family relations and early romantic involvement.…”
Section: Goals and Hypotheses Of The Present Studymentioning
confidence: 99%
“…Attachment theory has been extended to understand adolescent and adult romantic relationships as conscious manifestations of the attachment process, namely a typical style of relating or attachment style. This coherence across relationship history has received support: for example, adolescents' reported attachment quality to caregivers has been correlated with the quality of their (dating) relationships and the expectations they hold of marriage, with insecure attachment in adolescents related to negative (but not necessarily violent) dating experiences (Steinberg et al, 2006). Using the Adult Attachment Interview, Furman (2001) found that attachment styles are also related to working models of friendships.…”
Section: Maltreatment Attachment Processes and Dating Violence: Thementioning
confidence: 99%